Identification and characterization of microsatellites in ESTs of Rosa species: Insight in development of SSR markers - PANWAR, SAPNA; SINGH, KANWAR PAL; NAMITA, NAMITA; SONAH, HUMIRA; DESHMUKH, RUPESH K; SHARMA, T R (The Indian Journal of Agricultural Sciences, 2015)
The present investigations were undertaken during the year 2012. In this study, analysis of microsatellites identified in expressed sequence tags (ESTs) of Rosa species was performed. Entire set of ESTs for genus Rosa including 1 792 of Rosa chinensis, 5 495 of R.× hybrida and 1 849 of R. lucieae was retrieved from public database and assembled individually. Furthermore, 668 microsatellites (SSR) were identified in the 5 272 assembled ESTs in which di-nucleotide repeats were most frequent. The highest 55.2 percentage of di-nucleotide was identified in R. chinensis followed by R.× hybrida (50.1%) and R. lucieae (44.3%). Repeats with motif sequences AG/CT and AAG/CTT were observed as most frequent motifs. Moreover, SSRs were also identified in non-EST sequences available for the genus Rosa. The entire sequences were assembled together to develop non-redundant data that was subsequently used to design 293 SSR markers. Analysis of microsatellite and resource of SSR markers developed in present study will help for undertaking the molecular research in Rosa species.